(untitled) (Scientific journal of the Fergana State University, 2025)
The paper examines the influence of forest plantations on the properties of dark gray forest soils. The studies have shown that under different tree species growing on the same landscape element and close to each other, significant changes occur in the content and composition of organic matter formed during the decomposition of plant residues, in the cation exchange capacity and the degree of saturation with bases and a number of other soil properties. The structural composition of soils and the water resistance of aggregates also differ. The reasons for the changes occurring are apparently related to the distribution features of the root systems of tree species and the intensity of the biological cycle.